2011
DOI: 10.3390/medicina47070055
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Chronic Pain and Depressive Symptoms in Patients With Trigeminal Neuralgia

Abstract: Trigeminal neuralgia (TN) is a rare neuropathic disorder with an excruciating facial pain. The unpredictable pain attacks may result in anxiety and depression. The aim of this study was to determine and to evaluate the level of chronic facial pain and its association with the appearance of anxiety and depression. Materials and Methods. A total of 30 patients with TN and chronic facial pain (group A, 25 women and 5 men; mean age, 64.2±3.2 years) and 30 with atypical facial pain (group B, 26 women and 4 men; mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 26 publications
1
33
0
3
Order By: Relevance
“…Only 1 previous study has evaluated the prevalence of depression in 30 patients with TN; the incidence of depression reported was 76.7%. [10] Our results supported those from this study, indicating that the prevalence of depression and anxiety in TN is higher with chronic pain. Psychosocial intervention is therefore necessary for patients with TN.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Only 1 previous study has evaluated the prevalence of depression in 30 patients with TN; the incidence of depression reported was 76.7%. [10] Our results supported those from this study, indicating that the prevalence of depression and anxiety in TN is higher with chronic pain. Psychosocial intervention is therefore necessary for patients with TN.…”
Section: Discussionsupporting
confidence: 90%
“…Macianskyte et al [10] reported a higher level of anxiety and depression (96.67%) in patients with TN than in patients with atypical facial pain; however, only 26.7% patients with TN used psychotropic drugs. Further, Tolle et al [11] reported concomitant use of medication for anxiety and/or depression in only 33% of patients with TN, and less than 50% patients believed their prescription medications were effective.…”
Section: Introductionmentioning
confidence: 99%
“…The “pain affect” has also been described as the squeal of other physical and psychological disorders such as anxiety and depression (McWilliams et al, 2003, McWilliams et al, 2004, Maletic and Raison, 2009, Dellarole et al, 2014). These comorbidities have been so prevalent that approximately half of all patients suffering from chronic pain are also described as suffered from anxiety and depression (Asmundson and Katz, 2009, Asmundson and Taylor, 2009, Robinson et al, 2009, Macianskyte et al, 2011). The relationship between chronic pain, anxiety, and depression, is extremely complex with extensive overlap making it difficult to determine the cause and effect.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that chronic pain is associated with psychological symptoms and persistent central sensitization of the central nervous system 2 . Macianskyte et al 5 conducted a study with 30 patients with TN and chronic unspecified facial pain, and 30 patients with atypical facial pain. Subjects were evaluated for duration of pain, levels of anxiety and depression through the use of questionnaires.…”
Section: Discussionmentioning
confidence: 99%
“…The understanding and management of patients with chronic orofacial pain is probably the biggest challenge faced by professionals 2,3 . Individuals with chronic pain have a multifactorial problem with physical and psychosocial symptoms 4,5 . Recognizing the psychological components of pain is critical to conduct an effective treatment 6 .…”
Section: Introductionmentioning
confidence: 99%